Motivasi dan Kemampuan Kerja Karyawan Rumah Sakit Implikasinya pada Prestasi Kerja - Suharyanto Suharyanto (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2021)
Globalization has a big impact on the business world. One of the spearheads that must be owned by a company is qualified and capable human resources in their fields. One effort to improve the quality of human resources is to improve work efficiency and effectiveness so that employee performance increases, where performance is a function of motivation and ability (Gomes, 2000). Through the fulfillment of abilities and motivations that are believed to improve employee performance, in this case Lavalette Hospital and Malang Islamic Hospital employees. This study uses explanatory research with a questionnaire as the main tool for data collection. The data analysis uses multiple linear regression. The results of inferential analysis indicate that the variables of existence needs, relationship needs and needs to develop, technical abilities and behavioral abilities partially and simultaneously have a significant effect on employee performance. Variable technical ability and behavioral ability partially or simultaneously have a significant effect on employee work performance. Thus, the company must be able to maintain and improve motivation and ability of employees, especially for the needs of relationships and behavioral abilities because it has a dominant influence on employee performance.